Parity and the risk of incident dementia: a COSMIC study. (20th October 2020) - Bae, J. B.; Lipnicki, D. M.; Han, J. W.; Sachdev, P. S.; Kim, T. H.; Kwak, K. P.; Kim, B. J.; Kim, S. G.; Kim, J. L.; Moon, S. W.; Park, J. H.; Ryu, S.-H.; et al.
Abstract: Aims: To investigate the association between parity and the risk of incident dementia in women. Methods: We pooled baseline and follow-up data for community-dwelling women aged 60 or older from six population-based, prospective cohort studies from four European and two Asian countries. We investigated the association between parity and incident dementia using Cox proportional hazards regression models adjusted for age, educational level, hypertension, diabetes mellitus and cohort, with additional analysis by dementia subtype (Alzheimer dementia (AD) and non-Alzheimer dementia (NAD)). Results: Of 9756 women dementia-free at baseline, 7010 completed one or more follow-up assessments. The mean follow-up duration was 5.4 ± 3.1 years and dementia developed in 550 participants. The number of parities was associated with the risk of incident dementia (hazard ratio (HR) = 1.07, 95% confidence interval (CI) = 1.02–1.13). Grand multiparity (five or more parities) increased the risk of dementia by 30% compared to 1–4 parities (HR = 1.30, 95% CI = 1.02–1.67). The risk of NAD increased by 12% for every parity (HR = 1.12, 95% CI = 1.02–1.23) and by 60% for grand multiparity (HR = 1.60, 95% CI = 1.00–2.55), but the risk of AD was not significantly associated with parity. Conclusions: Grand multiparity is a significant risk factor for dementia in women. This may have particularly important implications for women in low and middle-income countries where the fertility rate and prevalence of grand multiparity are high.